PENERAPAN KURIKULUM MERDEKA BELAJAR DALAM MENGHADAPI ERA SOCIETY 5.0 DI SMP N 7 KOTA JAMBI - Salsabila Rohadatul Aisy; Safitri, Riesty; Rustam (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The implementation of the independent learning curriculum program in schools aims to develop human resources capable of welcoming the Society 5.0 era. This article is a literature review from a number of journals that are qualitatively relevant to the topic discussed. The steps taken by the author to collect readings in this article are (1) collecting data related to the topic of interest; (2) Summarize and prepare relevant main topics. The next generation will answer the challenges of the Society 5.0 era. The author's final result in this article is to show that the implementation of autonomous learning is appropriate in the Society 5.0 era. Creativity and innovation are skills that writers need to become strong, tough and persistent. Implementing independent learning programs in schools to improve the quality of education in Indonesia and prepare graduates to compete well in global competition.